2019
DOI: 10.1021/acs.jpca.9b00300
|View full text |Cite
|
Sign up to set email alerts
|

A Perfluorinated Carboxylic Sulfuric Anhydride: Microwave and Computational Studies of CF3COOSO2OH

Abstract: Trifluoroacetic sulfuric anhydride (CF 3 COOSO 2 OH, TFASA) and its deuterated isotopologue have been observed by pulsed-nozzle Fourier transform microwave spectroscopy. TFASA was generated in situ in a supersonic expansion from the reaction of CF 3 COOH or CF 3 COOD with SO 3 . The spectrum, which was notably weaker than those of previously studied carboxylic sulfuric anhydrides, is that of a simple asymmetric rotor with no evidence of internal rotation of the CF 3 group. Calculations at the M06-2X/6-311+ +G(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…However, with the inclusion of ZPE, the calculations indicate a barrierless process, with a zero-point corrected activation energy of only 0.01 kcal/mol. The imaginary frequency found at the transition state corresponds to the concerted π 2 + π 2 + σ 2 cycloaddition mechanism, as previously proposed. A diagram summarizing the relative energies at key points on the potential energy surface is given in Figure and numerical values are provided in Table .…”
Section: Propiolic Sulfuric Anhydridesupporting
confidence: 58%
See 2 more Smart Citations
“…However, with the inclusion of ZPE, the calculations indicate a barrierless process, with a zero-point corrected activation energy of only 0.01 kcal/mol. The imaginary frequency found at the transition state corresponds to the concerted π 2 + π 2 + σ 2 cycloaddition mechanism, as previously proposed. A diagram summarizing the relative energies at key points on the potential energy surface is given in Figure and numerical values are provided in Table .…”
Section: Propiolic Sulfuric Anhydridesupporting
confidence: 58%
“…Energy diagram depicting key points on the intermolecular potential surface for the formation of carboxylic sulfuric anhydrides that do not involve internal rotation. For the reaction with CH 3 COOH and CF 3 COOH, see refs and , respectively, for a more complete representation including internal rotation. Electronic energies are calculated at the CCSD­(T)/CBS­(D-T)//M06-2X/6-311++G­(3df,3pd) level of theory with zero-point corrections from M06-2X frequencies.…”
Section: Propiolic Sulfuric Anhydridementioning
confidence: 99%
See 1 more Smart Citation
“…It seems that the nucleation ability of carboxylic acid could be improved by the reaction with SO 3 , and the corresponding product carboxylic sulfuric anhydride is speculated to participate in NPF . The subsequent theoretical calculation on monocarboxylic acids suggested that different types of substituents such as −CHCH 2 , −CCH, −CF 3 , and the aldehyde group have little effect on the reaction energy barrier, ,, while for polycarboxylic acids, the energy barriers of reactions between one SO 3 and −COOH at different sites are all low enough for these reactions to take place in the gas phase . However, the kinetics of the sequential reaction of multiple −COOH with multiple SO 3 and their influence on NPF are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid meta-GGA functional M06-2X has been performed to study the different reactivity descriptors concerning IP, electronic a nity, hardness. This method has been proved to give the best correlation with experimental data [26,27]. The split-valence 6-311++G(2d, 2p) has been employed in this study.…”
Section: Methodsmentioning
confidence: 99%